Etnobotanical resources of the Multiple-use Guaraní Reserve, Misiones (Argentina): their importance to the indigenous communities of Caramelito and Taruma Poty - Keller, Hector Alejandro (2010)
The present results are of an ethnobotanical study of two Guarani communities Caramelito and Taruma Poty that use natural resources of the Guarani Multiple-Use Reserve. This is a protected area of 5343 hectares in Misiones, Argentina. The inhabitants of Caramelito belong to the Mbya branch of the Guarani, while those of Taruma Poty belong to Ava-Chiripa branch. An exhaustive floristic study enabled estimation of the proportion of plants used by members of these communities in relation to tot~ number ·of native plants in this reserve. The most important use categories are described and illustrated and a list of species is given with indigenous names, uses, habitats and the voucher herbarium specimens. This study showed that the Multiple-use Reserve is effective in supplying many essential resources for Guarani ·communities. Th~ authors urge better conservation of this area upon which the Guarani depend so extensively for their livelihood. In the Part-1 of the study, the Appendix includes monocots and dicots up to the family Asteraceae. Remaining information forms Part-11.